Combating COVID - 19: A look at prevention measures with an emphasis on social isolation (Research, Society and Development, 2020)
This study aimed to identify strategies to combat COVID-19, with an emphasis on social isolation. This is an integrative literature review study, with a qualitative approach, carried out by searching for articles indexed in the following databases: Scientific Electronic Library Online (SCIELO), National Center for Biotechnology Information (PUBMED), Latin Literature -American and Caribbean Health Sciences (LILACS). The inclusion criteria include literature review surveys covering the year 2020. The exclusion criteria were duplicate, incomplete articles, abstracts, reviews, debates, and experience reports. 05 articles and 04 studies referring to health entities were analyzed. The results of the study found that there are several strategies and recommendations that aim to combat and prevent the spread of COVID-19. So far, there are no drugs or other therapeutic measures to eradicate the disease. Several researches have been developed in this sense, as well as the evaluation and investigation of the effectiveness of existing drugs, to act in the fight against the new coronavirus. We conclude that the preventive measures against COVID - 19 are still not enough to fight the pandemic. Therefore, some preventive strategies are effective in reducing the number of suspected and confirmed cases of the disease, due to limited contact with society, resulting in the low transmission capacity of the virus.